Effect of different energy availability levels on nocturnal interstitial fluid glucose concentrations in elite triathletes - Hiromatsu, C.; Goto, K. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Triathletes are exposed to higher energetic demands, leading to increased risk of lowered energy availability (EA) compared with other types of athletes (Jesus et al., 2022). Sustained low EA (LEA) distributes both impairments of health and exercise performance (Mountjoy et al., 2023). Sedentary women in LEA state caused substantial decrease in nocturnal blood glucose and 24 h average blood glucose concentrations compared with those in sufficient energy balanced state (Loucks et al., 2003). However, the effect of different EA levels on 24 h glucose changes in elite endurance athletes is not clear. We examined the effect of different EA levels on 24 h changes in interstitial fluid glucose concentrations (IGC) in elite male triathletes during training camp. METHODS: Three elite male triathletes (athlete A, B, C) were continuously evaluated IGC changes for four consecutive days (days 1-4). Subjects recorded daily activities in detail. Training log was classified using METs, and exercise energy expenditure (EEE) were then estimated. To prevent overestimation, EEE was adjusted to remove calories contributed by resting energy expenditure for the duration of the exercise (Jesus et al., 2022). All subjects completed same training from days 1-3. On day 4, subjects conducted different training regimen individually. Energy and macronutrients intakes were evaluated by dietary survey. We could not measure IGC between 21:00 and 23:00 due to the error of measuring device. RESULTS: No significant relationship was found between EA and average nocturnal (0:00-7:00) IGC (r² = 0.039, p = 0.538). During 4 days, the relative time (%) of IGC above 100 mg/dL during the nocturnal time was substantially high, 100% for athlete A, 94% for athlete B, and 75% for athlete C, respectively. However, among the 4-day measurements of the three athletes, the lowest EA was observed concomitantly with the lowest average nocturnal IGC (EA, 18 kcal/kg FFM/day; IGC, 98±5mg/dL, athlete C on day 3). CONCLUSION: Sufficient IGC during night were maintained in male elite triathletes during training camp regardless of EA levels.